Utilization of Inpatient Mental Health Care in the Rhineland During the COVID-19 Pandemic - Jürgen Zielasek; Jürgen Vrinssen; Euphrosyne Gouzoulis-Mayfrank; Euphrosyne Gouzoulis-Mayfrank (Frontiers Media S.A., 2021)
Background: During the Coronavirus-19 (COVID-19) pandemic, considerable changes occurred in the utilization of mental health care.Objectives: We conducted an analysis of the changes of inpatient and day patient mental health care utilization in an association of psychiatric hospitals during the COVID-19 pandemic.Materials and Methods: We used the statistics database of the association of nine psychiatric hospitals of the Rhineland Regional Council (Landschaftsverband Rheinland, LVR). We compared the case numbers of spring 2019 and spring 2020 and analyzed alterations in the diagnostic spectrum. Finally, we analyzed the age, gender, and diagnoses of patients tested positive for COVID-19.Results: A total of 25,612 inpatient psychiatric hospital admissions were assessed. Case rates decreased by 25% during the COVID-19 pandemic. Changes varied between diagnostic groups, and there were even increases in case numbers for certain diagnoses. Women and patients of higher ages were overrepresented among psychiatric inpatients with COVID-19.Conclusions: The COVID-19 pandemic resulted in considerable reductions in the total number of mental health-care admissions and in changes in the diagnostic spectrum. The results may be explainable by deferrals of elective hospital admissions during the acute phase of the pandemic and by destabilizing effects of the pandemic and social distancing on people with mental disorders.